2006
DOI: 10.1292/jvms.68.1075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin Injected into the Third Ventricle on Growth Hormone Secretion in Holstein Steers

Abstract: ABSTRACT. The effects of melatonin (MEL) injection into the third ventricle (3V) on growth hormone (GH) secretion were investigated in conscious Holstein steers. A stainless steel cannula was stereotaxically implanted in the 3V based on the ventriculogram. In Exp. 1, three doses of MEL (100, 300 or 600 µg) were injected into the 3V through the cannula and the GH concentration after the injection was determined. In Exp. 2, intracerebroventricular (icv) and intravenous (iv) injections of MEL (100 µg) and GH-rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…However, our results showed that melatonin was at least in part involved in these mechanisms in goats, although controversial results (Valcavi et al . 1993; Kasuya et al . 2006) were reported on the effects of melatonin on the secretion of GH.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed that melatonin was at least in part involved in these mechanisms in goats, although controversial results (Valcavi et al . 1993; Kasuya et al . 2006) were reported on the effects of melatonin on the secretion of GH.…”
Section: Discussionmentioning
confidence: 99%
“…More than one month before the experiment, an 18 gauge stainless cannula (Eicom, Kyoto, Japan) was stereotaxically implanted into the third cerebral ventricle of each steer under isoflurane anesthesia according to a procedure reported earlier [7]. Briefly, the head of each steer was placed in a stereotaxic apparatus for calves [14].…”
Section: Methodsmentioning
confidence: 99%
“…These variations in the relationship between melatonin and GH might be due to multiple factors, such as differences in the physiological conditions, different actions depending on the species studied, experimental models used, etc. [21]. Many studies indicate a connection between pineal gland function and the GH/IGF-1 axis in mammals; however, their results are not always synonymous.…”
Section: Discussionmentioning
confidence: 99%